Prototype design of smart home system using internet of things - Gunawan, Teddy Surya; Husna Yaldi, Intan Rahmithul; Kartiwi, Mira; Ismail, Nanang; Za'bah, Nor Farahidah; Mansor, Hasmah; Nordin, Anis Nurashikin (Institute of Advanced Engineering and Science, 2017)
Smart home control system (SHCS) can be integrated into an existing home appliances to reduce the need for human intervention, increase security and energy efficiency. However, it is still an open problem due to difficulties such as network distance, signal interference, not user friendly, increased cost and power consumption. This paper reviews various topics on smart home technologies including control system, smart home network, smart home appliance and sensor technologies for smart home. In this research, the proposed prototype of home automation allows users to remotely switch on or off any household appliances based on Internet of Things (IoT) with the enhancement of solar charger. This prototype uses four types of sensors i.e. PIR sensor, temperature sensor, ultrasonic sensor and smoke gas sensor for automatic environmental control and intrusion detection. The hardware, software, and test field design will be discussed in this paper.